Refugees: the inequalities among the unequal (Management & Public Policies Journal, 2021)
The definition of "refugee" is changing, depending on the historical moment, political motivations, and social and historical context. This issue demands greater attention from states and governments, as well as from those engaged in the formulation of public policies.  This article addresses the literature on the situation of people in refugee situations, in general and in Brazil. In doing so, it highlights three special categories among them: stateless persons, illegal migrants, and gender, subdivided into women and LGBTI.